EVALUATING THE RELATIONSHIP BETWEEN TENDENCIES OF ORTHOREXIA NERVOSA AND BODY DISSATISFACTION AMONG ADULTS - Elif Esra Öztürk (Sabiad)
Objective: The aim of the study is to evaluate the relationship between the tendencies of orthorexia nervosa and body dissatisfaction among adults. Material and Methods: The study was conducted on 239 voluntary individuals who were aged between 19 and 64 years and residing in Gaziantep. While the ORTO-11 scale was used to assess the orthorexic tendencies of the participants, the body shape questionnaire (BSQ-34) was employed to assess their body dissatisfaction. Also the general characteristics, anthropometric measurements were collected. In ORTO11 scale, 25 points and below were considered as an orthorexic tendency. In the BSQ-34, a score between 80-110 points was classified as slight dissatisfaction, a score between 111-140 points as moderate dissatisfaction, and a score above 140 points as severe dissatisfaction. Results: ORTO-11 and BSQ-34 mean scores of the participants were 29.54±5.98 and 83.20±45.46, respectively. 27.6% of the participants had orthorexic tendencies and 40.6% had dissatisfaction (slight: 10.9%, moderate: 13.4%, severe: 16.3%). There was no statistically significant difference in the mean BSQ-34 scores of the participants based on the orthorexic tendency classification. Furthermore, according to the body dissatisfaction classification, there was no statistically significant difference between the participants’ mean ORTO-11 scores. However, the participants with severe dissatisfaction had significantly higher mean body weight and mean body mass index than those with no dissatisfaction. Conclusion: This study revealed that there was no correlation between tendency of orthorexia nervosa and body dissatisfaction. Further studies need to be conducted to verify the results